2010
DOI: 10.1089/ten.tea.2010.0009
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Strain Improves Strength and Function of a Collagen-Based Tissue-Engineered Vascular Media

Abstract: Tissue-engineered blood vessels may provide a solution to the lack of suitable blood vessels for coronary and peripheral vessel bypass grafting. Cyclic strain can be used to provide a more physiological environment that may result in tissue that more closely resembles native artery. In this study, cyclic strain is applied to a collagen-based, tissue-engineered vascular medium. An increased culture time was used to allow the tissue to adhere to the silastic sleeve and to eliminate longitudinal compaction. Cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 49 publications
1
48
1
Order By: Relevance
“…Since the microtissues anchor themselves to the cantilevers during their self assembly, our system allows in-situ testing without the perturbations to these delicate microscale specimens that would arise from transferring them to conventional mechanical testing systems, in which loading of specimens is laborious and a major source of variability. 32,33 Through prolonged culture, we further demonstrated the feasibility of using this system for long-term mechanobiological studies. Collectively, our system offers advantages over existing approaches by providing a novel window into the mechanics of tissue remodeling in real time.…”
Section: Discussionmentioning
confidence: 80%
“…Since the microtissues anchor themselves to the cantilevers during their self assembly, our system allows in-situ testing without the perturbations to these delicate microscale specimens that would arise from transferring them to conventional mechanical testing systems, in which loading of specimens is laborious and a major source of variability. 32,33 Through prolonged culture, we further demonstrated the feasibility of using this system for long-term mechanobiological studies. Collectively, our system offers advantages over existing approaches by providing a novel window into the mechanics of tissue remodeling in real time.…”
Section: Discussionmentioning
confidence: 80%
“…13 Mechanical strain is also known to be a potent factor in affecting cell function in a variety of tissues, 14,15 including cardiovascular tissues. 16,17 In these and other studies, strain has been shown to facilitate cell remodeling of 3D artificial tissues and have important effects on gene expression and cell function. In a study using neonatal rat heart cells in a supported fibrin matrix, it was found that application of cyclic strain increased collagen secretion in a manner that was dependent on the loading regimen.…”
mentioning
confidence: 88%
“…18 Mechanical strain also has been shown to improve the strength of collagenbased tissue analogs through increased expression of collagen and matrix compaction. 16,19 A smaller number of studies have also attempted to combine fluid shear and mechanical strain, for example, by exposing tissue-engineered heart valves to tangential fluid flow and cyclic tensile strain. 20 Another study combined interstitial fluid flow with compressive strain to study mineral formation in collagen gels.…”
mentioning
confidence: 99%
“…21,22 The impact of strain amplitude on SMCs and their matrix production has been previously reported in several studies. 16,19,23,24 Less is known about the impact of strain frequency, especially on elastic matrix generation by SMCs cultured with EFs. Thus, in this study we systematically varied the cyclic stretch frequency to determine its impact on SMC proliferation, phenotype, and ECM production.…”
Section: Figmentioning
confidence: 99%
“…21,22 To date, most studies that applied cyclic stretch regimens have primarily used strain levels of > 2.5%, and a majority of them have used 10% strains. 16,19,23,24 However, other studies have shown that cellular synthesis and enzymatic activity of the elastolytic protease matrix metalloproteinase-2 (MMP-2) are increased at such high strains. 25,26 While MMP-2 plays an important role in matrix turnover and healthy reorganization, 25 chronic enzymatic activity can degrade newly synthesized elastic matrix and prevent its maturation and assembly within the scaffolds.…”
mentioning
confidence: 99%